Earthworms in various agricultural and forest ecosystems in São Carlos—SP, Brazil - Bruz, Lilianne Dos Santos Maia; Santos, Alessandra; Demetrio, Wilian C.; de Freitas Primo, Daniele; Feliciano, Luana Priscila; Fernandes, Carlos Henrique; Bartz, Marie L. C.; de Campo Bernardi, Alberto Carlos; Pezzopane, José Ricardo Macedo; Brown, George Gardner (Zootaxa, 2023)
Integrated agricultural systems have been greatly expanding in Brazil and currently cover over 30 million hectares. Although these land use systems help soil and environmental quality, little is known of their impacts on earthworm communities. In the present study we evaluated earthworm abundance, biomass and species richness in various integrated and conventional agricultural production systems (pasture, crops), as well as native forest and Eucalyptus plantations. The research was carried out at Fazenda Canchim (Embrapa Livestock Southeast) and at the neighboring campus of the University de São Carlos (UFSCar), in São Carlos municipality in São Paulo state, Brazil. Two earthworm sampling methods, i.e., quantitative (25 x 25 x 20 cm deep monoliths) and qualitative (holes of similar size and niche sampling), were used in three integrated production systems, three conventional systems and two forest systems, totaling 232 quantitative samples and over 160 qualitative samples. Earthworms were counted and identified using available keys. Eight earthworm species of five families (Rhinodrilidae, Ocnerodrilidae, Megascolecidae, Benhamiidae and Glossoscolecidae) were found, with most of the 2,145 individuals being exotic or peregrine species, particularly Pontoscolex corethrurus (88% of total) and various Dichogaster spp. (8% of total). Two native species were encountered in low abundance (55 individuals), both of which are new to science (Fimoscolex n.sp.7 and Glossoscolex n.sp.9) and must still be formally described. The new species were found in the agricultural systems, but not in the native forest and the Eucalyptus plantation, where P. corethrurus and Megascolecids predominated. One unidentified Ocnerodrilid sp. was found only in the intensive pasture. Species richness was highest in the intensive pasture (7 spp.), followed by the agrosilvopastoral and agropastoral systems, highlighting the importance of integrated and pastoral systems in preserving earthworm richness and native species.